Critobulus of Imbros: the historian of perished world - Kotłowska, Anna (Balcanica Posnaniensia. Acta et studia, 2022)
The aim of paper is to present wrtitings composed by Critobulus of Imbros, together which some remarks, especially from historiosophical point of view. For him the most important thing was to explain halosis in terms of traditional Byzantine historiosophy.